Fermentability characteristics of different Saccharomyces cerevisiae cell wall using cat faeces as inoculum. Issue 1 (14th December 2020) - Calabrò, Serena; Musco, Nadia; Roberti, Fernando; Vastolo, Alessandro; Coppola, Mario; Esposito, Luigi; Cutrignelli, Monica Isabella
Abstract: Yeast cell wall are a source of prebiotics in animal nutrition, able to improve microbial function in the large intestine. The purpose of this paper was to compare the fermentability of six Saccharomyces cerevisiae (SC) cell wall obtained from three production processes (alcoholic, brewers and bakers). For each production process the two aliquots characterised by the highest the lowest carbohydrate levels were selected. In order to perform the in vitro trial, each SC substrate was incubated at 39 °C under anaerobic condition for 72 h, using cat faecal inoculum . The results showed that the production processes did not affect organic matter disappearance, while significantly ( p  < .01) influenced cumulative volume of gas which appeared the lowest for alcoholic substrates. The alcoholic SC substrate showed significantly highest ( p  < .01) fermentation rate. All SCFA were affected by the production processes ( p  < .01). In particular, brewers substrates showed the highest acetate and butyrate production, while the fermentation of SC cell wall obtained by bakers showed the highest production of valerate, iso-butyrate and iso-valerate. Considering the high fermentability and acetate and butyrate production, the SC cell wall obtained by brewers seem more suitable to be used as prebiotic in cat diet. The bakers extract seems less advisable, due to its less fermentability at which corresponded the highest production of gas and iso-butyrate and iso-valerate, which are considered the less desirable end-products. The study underlines that it is necessary to evaluate the fermentation characteristics of these ingredients before their use in diet formulation as source of prebiotics. Highlights: The production process affects the in vitro fermentation parameters differently from the carbohydrate's concentration. The production processes significantly influenced cumulative volume of gas and all short chain fatty acids production. The SC cell walls obtained by brewers seem more suitable to be used as prebiotic in cat diet and the bakers extract seems the less advisable.